Youth on Freedom of Religion or Belief in Sri Lanka A Study of an Online Opinion Survey - Subasinghe, N.P.; Jeevasuthan, S.; Jayasena, I.M.; Amarasinghe, S.; Ariyawansa, S. (FORB, 2021)
Sri Lanka is a multi-ethnic and religious country that has gone through many sorts of social and political conflicts during the past few decades. Ethnicity or religion has become a cause of conflict all the time. After 26 years of armed conflict, the ethnic tension shifted and converted into religious tension. While all the population was facing different types of conflicts, especially the youth population was more involved in all sorts of social activities. Education, social motives, age, attitude, and opinions are some of the fundamentals which encourage youth to be involved in socio-political activities today. While having tension and mistrust among different religious groups, the freedom of religion or beliefs of people were challenged. Some religious groups were targeted negatively when there was social tension such as the Easter Sunday attack in 2019 and the recent Covid-19 pandemic in Sri Lanka. This online survey on Youth and Freedom of Religion or Belief (FORB) is to assess the knowledge, attitudes, practices, and the associated factors on FORB among the youth of Sri Lanka. It was found that more than 20% of youth have faced violence or discrimination against the FORB. Furthermore, they were not capable enough to take sustainable action to prevent or combat such incidents. Though some of the youth have tried to combat violence against FORB as they were stuck in personal and social level issues. The youth finds lots of challenges when they enjoy their FORB. For instance, religion has been given by birth and it is so hard to leave or change on their own will. There is no sufficient motivation, platforms, or space for youth to enjoy their FORB. There are policy-level weaknesses such as the minority religions or language groups are not equally treated in the common social spaces. For instance, some university students were facing violence against religion or belief. There were certain suggestions to strengthen youth in FORB. Best uses of social media platforms are raising awareness among youth on FORB, inter-religious activities and also including religion in the school syllabus. These were some of the suggestions that came up by the youth. However, these suggestions can be strong enough when there is a supportive policy background and a culture in Sri Lanka. Therefore, religious institutional performance, social and attitude change as well as the revision of the law and order is required to strengthen youth on FORB in Sri Lanka.
Keywords: Youth; Freedom; Religion; Belief; Challenges; Opportunities; Suggestions